Artificial-Nest Rainwater-Harvesting with Fishery and Floating-or-Rooftop-Gardening Act as 21st Century COVID-19 Epidemic-Model: Improved Biodiversity Agriculture Socio-Economic Civil-Engineering Environmental-Sciences Technology-Communication - Subhas Chandra Datta (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2020)
Introduction: The past-two-decades have faced many-viral-epidemics. The present threat-COVID-19 causes great-loss of human-lives, change human-civilization, public health, agriculture, travel, socioeconomic, education, civil-engineering, environmental-sciences and clinical-research also. There are no proper-effective-treatment-methods. The low-income-households, senior-citizens, and street-children are not able to manage. So the whole world as well as the Government of India tries to reorient for the COVID-19 epidemic-crisis, by developing policy-initiative. So it is emphasis on the conservation of biodiversity, agriculture, socio-economic, civil-engineering, and environmental-sciences, for preventive-measures against "21st century-various-human-diseases like COVID-19-Pandemic". Methods: In the two ecofriendly localities; rural and urban areas, where constructs or set up different types of artificial-nests in the building as well as in the trees, rainwater-harvesting with fishery, and nutritional-garden, forming the common-complex-ecosystem with landscaping by trees, garden, midday-meals, store-grains reservoir's, playground, pond, and river with agriculture.  Result: Various kinds of birds, rats, mice, moles, bats, squirrels, mongooses, insets, toads, snakes, and other animals, are the regular visitors. But the owls apparently act as a keystone-species within these food-chain-relationships. Rats that happen to spoil food items of mid-day-meals, store-rooms, and documents are checked by barn-owl. Bats make building dirty by their excreta are also controlled by this owl. Different pests and mongoose, which are found to significantly reduce food production in agriculture, pisciculture, tsar-industries, hatcheries, and poultry-farm, are appreciably kept on top of things. And, improves midday-meal, arouses the interest of locality on ecology-food-chain-relationships-issues, and contributes to sustainable-pisciculture-pond, agriculture, and kitchen-garden-management, micro-and macro- climate issues, and also community-health also. It's worth mentioning that the hooter plays the role of the simplest carnivore, predating on mongoose juveniles and bats, the carrier of coronavirus, again confirming the "Biological and Bio-System-Engineering-Owl Controlled COVID-19 Engineering Bio-mechanical Biomedical-Science-Technology-Communication-Enriched-Agriculture-Environment with Joyful-Environment and Bat Secrets of Immunity Could Confirm the Clues to Treating-COVID-19". Conclusion: So the artificial-nest, rainwater-harvesting with fishery and floating-gardening shaded by solar-panel supplying-electricity for oxygen-producing-motor in water, OR rooftop-gardening attached with 'Bird's-/ Sky-Observer-Balcony', act as 21st-century civil-engineering COVID-19-epidemic-model which improved biodiversity, agriculture, environmental-sciences, technology-communication, socio-economy-welfare, developing the future-policy; the theme "Vision-2040" that would retain the human civilization's in old-forms because "Happiness brings good-health-and-wellbeing with the help of civil-engineering-and-environmental-biologist".